Experimental, numerical simulation and mathematical modelling of vane type vertical axis wind turbine - Al-Zaedy, Kadhim Hussein Suffer (School of Manufacturing Engineering, 2016)
Based on the problem statement, the following objectives are to be achieved; to perform experimental tests and to study the performance of the VVAWT for three and four blades, with closed and open vane designs; to measure the electric power output from the three- and four-blade VVAWT models with open vanes, using transmission gear and electric generator attached to the designs; to perform numerical simulations of the VVAWT models (three and four blades) for different angular positions of the blades and upstream air flow velocities for (i) all vanes closed and (ii) movable vanes. Using CFD software, the coefficient of drag CD and the aerodynamic characteristics of the VVAWT (distribution of static pressure, velocity, and turbulent kinetic energy) will be predicted; to develop a mathematical model for torque calculation of the VVAWT under the effect of wind shadow for three- and four-blade VVAWT models with open vanes.